Reaching Absent and Refusing Individuals During Home-Based HIV Testing Through Self-Testing—at What Cost? - Amstutz, Alain; Matsela, Lineo; Lejone, Thabo Ishmael; Kopo, Mathebe; Glass, Tracy Renée; Labhardt, Niklaus Daniel (Frontiers in Medicine, 2021)
Introduction: In the HOSENG trial (NCT03598686), the secondary distribution of oral self-tests for persons absent or refusing to test during a home-based HIV testing campaign in rural Lesotho resulted in an increase in testing coverage of 21% compared to a testing campaign without secondary distribution. This study aims to determine the per patient costs of both HOSENG trial arms. Method: We conducted a micro-costing study to estimate the cost of home-based HIV testing with (HOSENG intervention arm) and without (HOSENG control arm) secondary self-test distribution from a provider's perspective. A mixture of top-down and bottom-up costing was used. We estimated both the financial and economic per patient costs of each possible testing cascade scenario. The costs were adjusted to 2018 US. Results: The overall provider cost for delivering the home-based HIV testing with secondary distribution was US36,481 among the 4,174 persons enumerated and 3,094 eligible for testing in the intervention villages compared to US28,620 for 3,642 persons enumerated and 2,727 eligible for testing in the control. The cost per person eligible for testing was US11.79 in the intervention vs. US10.50 in the control. This difference was mainly driven by the cost of distributed oral self-tests. The cost per person tested was, however, lower in intervention villages (US15.70 vs. US22.15) due to the higher testing coverage achieved through self-test distribution. The cost per person confirmed new HIV+ was US889.79 in the intervention and US753.17 in the control. Conclusion: During home-based HIV testing in Lesotho, the secondary distribution of self-tests for persons absent or refusing to test during the visit reduced the costs per person tested and thus presents a promising add-on for such campaigns. Trial Registration:https://ClinicalTrials.gov/, identifier: NCT03598686